The pious sex catholic constructions of masculinity and femininity in Belgium c. 1800 - 1940. - van Osselaer, Tine.; Pasture, Patrick; K.U.Leuven. Faculteit Letteren. Subfaculteit Geschiedenis (Leuven K.U.Leuven. Faculteit Letteren, 2009)
The pious sex. Catholic constructions of masculinity and femininity in Belgium (c. 1800 - 1940) This study has a double goal. On the one hand it wants to improve the knowledge of Catholic constructions of masculinity and femininity in Belgium. On the other hand, by studying these gender constructions, it wants reconsider the feminisation thesis. This thesis has developed in historical research into a container term that covers various contents. It points not only at a numeric preponderance of women in the religious field, but also at content changes and at a quasi-identification of femininity and religiosity. The nineteenth-century feminisation of Christianity has been studied and documented in various European countries and denominations, but in the research on Belgian Catholicism it has not yet been a major theme. Still, Belgian society offers an interesting case as the Catholic realm covered a wide range of activities.
As such, women and men could confirm their Catholic identity in both public and more private fields. This study therefore focuses on the Belgian case, and more specific on the way in which gender differentiation was created and expressed. Focus is put on the Catholic adult laity and his or her (ideal) image in the Sacred Heart devotion, Catholic Action and sermons. These perspectives offer the opportunity to point at the diversity and the flexibility of these gender constructions. The construction of the Catholic man in the discourse of the Apostolat de la Prière (a devotional movement dedicated to the Sacred Heart) for instance illustrates how masculinity and emotionality were not necessarily considered mutually exclusive. This nineteenth-century emotionally expressive masculinity therefore makes it hard to define the nineteenth-century Sacred Heart devotion as feminised on the ground of her emotionality and sentimentality, as has been suggested in other studies.
Terms such as feminisation and the parallel masculinisation not only come close to an essentialist vision, they also seem to point at a kind of permanent construction of masculinity and femininity whereas in current gender research stress is put on the historical, social and geographical flexibility of gender constructions. Furthermore the stereotype of the pious sex appears to be older than the nineteenth century and it was not always used in a positive way in Catholic sources of the nineteenth- and twentieth century. The Catholic clergy noted the preponderance of women in religious practices also in the seventeenth century. The clergys observation of mens smaller interest in the religious field crystallised into a narrative of loss by the end of the nineteenth century; it incited men-oriented initiatives and (re)definitions of religion as masculine.
Similar initiatives have been described in other research as masculinisation, but as indicated this term is confusing. In order to be able to grasp in historical research this special attention for mens involvement, this study suggests stepping away from the somewhat confining terms feminisation and masculinisation and put the emphasis on differentiation instead, the creation of the difference. This offers the opportunity to describe the increasing attention for gender difference as can be remarked in the evolution of the mixed Apostolat de la Prière movement into the gender-exclusive Leagues of the Sacred Heart. Moreover, men do not necessarily have to oppose women: Catholic men can be compared to other men, e.g. socialist men. By shifting the attention towards differentiation, other categories such as class can receive ample attention and e.g. the evolution of the originally workers-oriented L
Dissertation submitted [...] in partial fulfilment of the requirements for the degree of Doctor in history
Keywords: Theses